Teaching Modern Multithreading in CS2 with Actors - Lewis, Mark C.; Lacher, Lisa L. (2020 IEEE International Parallel and Distributed Processing Symposium Workshops (IPDPSW), 2020)
Explosive growth in multiprocessor computing and the pervasive nature of multicore processors has not only made multithreading and related topics such as parallelism, concurrency, synchronization, etc. an essential part of any undergraduate Computer Science curriculum, it has also lead to the addition of newer constructs to support multithreading in many languages. Not only is it important to motivate student interest in this topic, it is important that they are also educated in current methods used in industry. This can mean an increase in material that needs to be covered. Because of the increase in scope of a CS education, teaching topics in parallel and distributed computing in a hands-on manner is challenging, thus it is valuable for educators to explore different methods of educational delivery in order to best engage their students within the limits of curriculum timelines. The actor model is immensely popular in industry and runs some of the most important software today. In this paper, we describe how we are using Actors as a significant part of the multithreading coverage at the CS2 level, for first-year computer science majors. We also describe a semester-long project that involves the use of these concepts to help solidify student understanding and present student feedback on the project and approach.